1992
DOI: 10.1063/1.350803
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and conditions for anomalous strain relaxation in graded thin films and superlattices

Abstract: Compositionally graded films of SiGe/Si(100) and GaInAs/GaAs were grown under different conditions in order to investigate the different modes of strain relaxation associated with the compositional grading. We show that, when the growth conditions are very clean and the gradient is shallow enough (about 1% misfit per half micron), very good, relaxed films are obtained. This coincides with the introduction of large numbers of dislocations in the substrate itself, which is counter-intuitive at first since the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
96
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(97 citation statements)
references
References 24 publications
1
96
0
Order By: Relevance
“…The use of compositionally graded buffer layers has led to a dramatic decrease in the threading dislocation density in such substrates. 1 Such buffer layers have enabled two-dimensional electron mobilities, confined within tensile strained Si channels, of 5.2ϫ10 5 and 2600 cm 2 /V s to be achieved at 0.14 and 300 K, respectively. 2,3 Such high mobility heterostructures are of great interest for metal-oxide semiconductor ͑MOS͒ and microwave applications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of compositionally graded buffer layers has led to a dramatic decrease in the threading dislocation density in such substrates. 1 Such buffer layers have enabled two-dimensional electron mobilities, confined within tensile strained Si channels, of 5.2ϫ10 5 and 2600 cm 2 /V s to be achieved at 0.14 and 300 K, respectively. 2,3 Such high mobility heterostructures are of great interest for metal-oxide semiconductor ͑MOS͒ and microwave applications.…”
mentioning
confidence: 99%
“…Such pile-ups are characteristic of the modified Frank-Read ͑MFR͒ relaxation mechanism proposed by LeGoues. 1 As the lateral dimension of the growth zone increases, an increased number of misfit dislocations are required to traverse the mesa in order to relax the structure. This results in an increased probability of an extending misfit encountering a pre-existing orthogonal dislocation on the same atomic plane of the graded buffer.…”
mentioning
confidence: 99%
“…For example, a 50 nm thick layer of Si 0.5 Ge 0.5 grown on Si at 550°C was measured to be 60% relaxed, which increased to 95% for a thickness of 120 nm, 12 and a 45 nm layer of Si 0.4 Ge 0.6 was found to be 71% relaxed. 13 In both cases, relaxation was observed to occur via a combination of the modified Frank-Read ͑MFR͒ multiplication mechanism 14 and surface roughening in the form of a threedimensional island formation. 15 To find the origin of the much greater stability and understand the relaxation processes in these tensile strained Si layers, we have employed AFM and XTEM.…”
mentioning
confidence: 99%
“…After annealing, the number of nucleated microtwins observable in the 70 nm layer does not significantly increase; however, 60°misfit dislocations are observed below the misfit interface. This could be due to the early stages of the MFR mechanism, 14 in which dislocations are injected into the substrate through multiplication events. It is suggested that this multiplication process, rather than an increase in the density of microtwins or stacking faults, is responsible for the increased relaxation at 70 nm after annealing evident in Fig.…”
mentioning
confidence: 99%
“…One problem with the linearly graded virtual substrate is that the mechanism most commonly responsible for relaxation, the modified Frank-Read ͑MFR͒ mechanism, 4 generates many dislocations from a few well-spaced sources. This causes dislocations to be piled up on the same ͑111͒ atomic glide planes.…”
mentioning
confidence: 99%